Optimizing Budget Deficit in Multi-Construction Projects Using Sequential Quadratic Programming - Hasan Musaab Falih; Sodani Noor A. Abdul-Jabbar Al; Salih Jihan Maan; Mohammed Sawsan Rasheed (Civil and Environmental Engineering)
Construction companies frequently struggle with poor cash flow management of their projects. Financial terms, including retainage, advance payments, and interest rates, significantly impact the project’s cash flow. This study investigates the financial aspects of projects with close beginnings. In addition, considers how to deal with financial deficits by suggesting a multi-project scheduling optimization model to minimize maximum negative cash flow while maintaining maximum profit. Sequential quadratic programming algorithms (SQP) generate workable schedules that optimally use available resources. Several scenarios have been used to test and examine the model. The outcomes indicate a decrease in negative cash flow for company 1 from (-1,852,096) to (-1,817,485) and for company 2 from (-484,524) to (-459,769) in scenario 1. Furthermore, a decrease in negative cash flow to (-1,661,660) alongside a profit of (776,593) for company 1 and a decrease to (-434,970) alongside a profit of (141,228) for company 2 in scenario 2. On the other hand, a decrease in negative cash flow to (-1,698,992) alongside a profit of (786,243) for company 1 and a decrease to (-370,815) alongside a profit of (209,363) for company 2 in scenario 3.